2006
DOI: 10.1007/bf03325948
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment due to rural electrification in hill tract of Bangladesh for sustainable development

Abstract: ABSTRACT:Environmental impact assessment (EIA) of any project is essential for understanding the sustainability of the project. For sustainable development of hill tracts, electricity is inseparable. Like other parts of Bangladesh hill tracts districts felt increasing demand of electricity. In this paper an attempt has been taken to present the existing environmental condition and analysis the future environmental condition after implementation of project. Electrification will extend the length of the active d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Commonly occurring pollution sources in the lake were oil and fecal from water transportations and from all sorts of thrown materials including solid wastes by many unconscious visitors. Alam et al (2006) reported that dissolve oxygen in Kaptai reservoir ranged from 5 to 6 mg⋅L -1 for average value of the whole depth, which remained mostly uniform in different water depths in the rainy season. As the water surface warms up in the dry season, oxygen depletion occurs in the deeper layer up to a depth of 8 to 15 m, which again shows cooling effect from mid May through rainfall.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Commonly occurring pollution sources in the lake were oil and fecal from water transportations and from all sorts of thrown materials including solid wastes by many unconscious visitors. Alam et al (2006) reported that dissolve oxygen in Kaptai reservoir ranged from 5 to 6 mg⋅L -1 for average value of the whole depth, which remained mostly uniform in different water depths in the rainy season. As the water surface warms up in the dry season, oxygen depletion occurs in the deeper layer up to a depth of 8 to 15 m, which again shows cooling effect from mid May through rainfall.…”
Section: Resultsmentioning
confidence: 98%
“…At present land use changes, urban human habitation, inland navigation, tourism activity, as well as major development scheme in terms of road, bridge and other construction work are greatly affecting this fresh water resource. Available published literature show that previous studies on Kaptai Lake were on physical and chemical limnology by Khan and Chowdhury (1994), macro-benthic invertebrate fauna by Khan et al (1996), population biology and environment of two carps by Azadi (1997), and environmental impact assessment by Alam et al (2006). Under the changed conditions and pressures over time in CHTs as described above, this study was undertaken to evaluate water quality of the reservoir.…”
Section: Introductionmentioning
confidence: 98%
“…Previous research on Kaptai Lake included physical and chemical limnology by Khan and Chowdhury (1994), macro-benthic invertebrate fauna by Khan et al (1996), population biology and environment of two carps by Azadi et al (1997), and environmental impact assessment by Alam et al (2006). Although there are a few publications on the physical and chemical limnology of Kaptai Lake, a full study on the seasonal change of water quality (physical, chemical, biological, and anionic) parameters as well as the trophic status index (TSI) in Kaptai Lake is sorely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although very recently, solar home systems have been introduced there, the electricity generation is far from sufficient to meet the ever-growing load demand. Hence, there is a dire need for establishing off-grid solar-powered plants to electrify these hilly areas [4].…”
Section: Introductionmentioning
confidence: 99%